Electronic waste collection incentivization scheme based on the blockchain - Alarood, Ala Abdulsalam; Abubakar, Adamu; Abdulrahman, Alzahrani; Faisal, Alsubaei (MDPI, 2023)
The approaches of motivating people for the collection of electronic waste (e-waste) are often insufficient due to inadequate methods of given incentives. Prior research studies have been carried out to tackle the issue of e-waste management in a broad sense. The findings of those studies indicated diverse strategies, each of which is relevant solely to a restricted range of electronic e-waste reprocessing circumstances. The current study has presented a proposed technique for incentivizing tasks and activities associated with the collection of e-waste through the adoption of the vector space technique. The method this research undertakes lies with utilizing blockchain smart contract technology. The reason for selecting this approach lies with the mapping of tasks, the nature of activities, and their magnitude, in order to derived an incentive. While the vector space model defines the set of tasks with their corresponding incentives, blockchain smart contract maps them together and establishes them in a record. Experimental scenarios for the calculation of incentives are presented; the findings reveal that among many scenarios of allocating incentives for e-waste collection, the best case is by utilizing a weighting scale scheme where each task and activity is mapped to its associated incentive rather than providing fixed incentive values. Ethereum was used as a digital token for each unit of incentive. This concept has contributed in encouraging personal accountability in the management of e-waste collection in order to cultivate sustainable behaviors for a long-term solution.